Histochemical Abnormalities in Various Forms of Congenital Muscular Dystrophy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
A large Australasian cohort of patients with congenital muscular dystrophy (CMD) was screened to determine the frequency of various forms, in a study at Children's Hospital at Westmead; the University of Sydney; University of Melbourne, Australia; and University of Nevada, Reno; and University of Illinois, Chicago.